A Bibliometric Study of the Publication Patterns of Scientists in South Africa 1992-96 - Daisy Jacobs (Information Research: An International Electronic Journal)
A bibliometric study of the publication patterns of a selected group of academic and research scientists of ten universities of South Africa for a period of five years, 1992-96. The subject fields surveyed are Physics, Chemistry, Plant and animal Sciences, and Microbiology/Biochemistry. These ten universities vary considerably with respect to standards of education, quantity of research and publication and overall progress. The general purpose of the study is 1) to determine whether academic status and prestige have any impact on the level of productivity, 2) to study the productivity within different areas of science, 3) to investigate whether or not the level of funding and/or the prospects of getting funded has any influence on the level of productivity in each area of science and their pattern of publication. The study collected two sets of data through a scientometric analysis of science citation index and a questionnaire. The study demonstrates that there is a direct relationship between status and publication productivity. The study further shows that there are significant differences in productivity between areas of sciences but that there is no direct relationship between institutional funding and productivity.